2016
DOI: 10.3847/0004-637x/831/1/101
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Emission Rings in Protoplanetary Disks Induced by Dust Evolution

Abstract: We report observations of resolved C 2 H emission rings within the gas-rich protoplanetary disks of TWHya and DMTau using the Atacama Large Millimeter Array. In each case the emission ring is found to arise at the edge of the observable disk of millimeter-sized grains (pebbles) traced by submillimeter-wave continuum emission. In addition, we detect a C 3 H 2 emission ring with an identical spatial distribution to C 2 H in the TWHya disk. This suggests that these are hydrocarbon rings (i.e., not limited to C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
293
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 215 publications
(330 citation statements)
references
References 104 publications
31
293
6
Order By: Relevance
“…Using models that include detailed modeling of the CO and H 2 O chemistry, studies found that the disk surrounding TW Hya is genuinely depleted in volatile carbon and oxygen (e.g., Bergin et al 2010;Bergin et al 2013;Hogerheijde et al 2011;Favre et al 2013;Du et al 2015). Recent observations of [CI], [CII], [OI], C 2 H and C 3 H 2 have reinforced this conclusion (Kama et al 2016b;Bergin et al 2016). …”
Section: Case Study: Tw Hyamentioning
confidence: 68%
See 3 more Smart Citations
“…Using models that include detailed modeling of the CO and H 2 O chemistry, studies found that the disk surrounding TW Hya is genuinely depleted in volatile carbon and oxygen (e.g., Bergin et al 2010;Bergin et al 2013;Hogerheijde et al 2011;Favre et al 2013;Du et al 2015). Recent observations of [CI], [CII], [OI], C 2 H and C 3 H 2 have reinforced this conclusion (Kama et al 2016b;Bergin et al 2016). …”
Section: Case Study: Tw Hyamentioning
confidence: 68%
“…Of particular interest is the protoplanetary disk of TW Hya (59.54 ± 1.45 pc, Astraatmadja & Bailer-Jones 2016), where the gas mass estimated using HD is more than one order of magnitude higher than the gas mass estimated using C 18 O (Favre et al 2013). Different studies have shown that the TW Hya disk seems genuinely depleted in volatile carbon and oxygen (e.g., Bergin et al 2010;Bergin et al 2013Bergin et al , 2016Hogerheijde et al 2011;Favre et al 2013;Du et al 2015;Kama et al 2016b). Recently, new observations of the CO isotopologues have become available (see, e.g., Schwarz et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disk displays a variety of substructures and radial morphologies in scattered light (Debes et al 2013;Akiyama et al 2015;Rapson et al 2015;van Boekel et al in press. ), mmdust continuum (Andrews et al 2012;Menu et al 2014;Andrews et al 2016;Tsukagoshi et al 2016) and molecular line emission (Qi et al 2013;Kastner et al 2015;Nomura et al 2016;Schwarz et al 2016;Bergin et al 2016), with many physical and chemical processes being invoked to explain these striking features.…”
Section: Introductionmentioning
confidence: 99%